Dataset: Digital Forensics and Artificial Intelligence: A Decade of Progress and Trends (2012-2022) - Febriandi Berutu; Mochammad Tanzil Multazam (Proceedings of The ICECRS, 2022)
This data article aims to streamline research on Digital Forensics and Artificial Intelligence by providing a comprehensive dataset derived from Lens.org. Using a three-step filtering process based on document type, publication date range, and subject matter, a total of 76 articles published between 2012 and 2022 were extracted. The analysis revealed that the University of Lausanne was the top institution, computer science was the dominant field of study, and the United Kingdom was the most active region in this domain. This dataset is valuable for researchers and practitioners seeking insights into the digital forensics and artificial intelligence landscape. Highlights: Comprehensive dataset of 76 articles in digital forensics and artificial intelligence from 2012 to 2022. Analysis reveals top institutions, fields of study, and most active regions in the domain. Valuable resource for researchers seeking insights into the digital forensics and AI landscape.